PENGARUH LATIHAN SELFTALK DAN IMAGERY TERHADAP KEMAMPUAN HASIL PERMAINAN BOLA VOLI PANTAI PADA ATLET VOLI PANTAI KOTA TEGAL - Lintang Maharani Putri; Sungkowo Sungkowo (Universitas Negeri Semarang, 2022)
Beach ball games are sports that require more conditions than indoor footballs generally due to heavier rules and venues. So not only is the physical better but the mental must also be considered. Selftalk and Imagery's mental training affects the game (attack and serve) of the beach ball. Formula problem 1) Is there an effect of selftalk training on the ability of the game of the beach ball athlete of Tegal city? 2) Is there an influence of imagery training on the playing ability of football athletes on the beaches of Tegal cities? 3) Is there effectiveness of selftalk and imagery exercises against the gaming ability of the city's beaches? The aim is to influence the significant influence and effectiveness of Selftalk and Imagery mental training on the ability of the beach ball game of Tegal City athletes. Researchers use experimental research methods with matching by subject design research design. The population in this study was 8 Bolavoli Athletes of Tegal City Beach. The sample withdrawal technique used by Purposive Sampling is a sample determination technique using certain considerations or characteristics. The results of the study data in the analysis used the Shapiro-Wilk Normality Test, Homogeneity Test, multiple linear regression test, paired t test and independent t test. Result 1) there is a significant influence, with a count of 14,967 > t tables 2,446, and significance values of 0.001 < 0.05 in selftalk exercises 2) there are significant influences, with t calculated result of 6,789 > t tables 2,446, and significance values of 0.007 < 0.05 in imagery drills 3) looking at effectiveness, selftalk exercises are better than imagery imagery Because the resulting number is 0.001 because it is close to the number 0. The conclusion of this study is that there is a significant influence and effectivity of selftalk and imagery exercises on the ability of the game, especially attack and service techniques in beach volleyball athletes of Tegal City. The advice and conclusion above is that coaches are able to make additional exercises that are useful to improve their abilities and develop a better training program for the mental improvement of athletes.